Love on the line [large type] - Gist, Deeanne (Thorndike Press large print Christian romance, 2012)
In 1904 Texas Ranger Luke Palmer arrives in Brenham, Texas, with one goal - to capture the gang of outlaws led by Frank Comer. Undercover as a telephone repairman, he uses his days on the range to search, not realizing there's another pair of eyes watching him. Switchboard operator Georgie Gail is on a birding expedition. But instead of sighting a painted bunting, her opera glasses capture her telephone man, armed and far away from telephone lines. Palmer is forced to take this alluring troublemaker into his confidence . . .